2011
DOI: 10.1080/17533015.2010.551716
|View full text |Cite
|
Sign up to set email alerts
|

Arts practices in unreasonable doubt? Reflections on understandings of arts practices in healthcare contexts

Abstract: This article suggests that the discourse on arts and health encompass contemporary arts practices as an active and engaged analytical activity. Distinctions between arts therapy and arts practice are made to suggest that clinical evidence-based evaluation, while appropriate for arts therapy, is not appropriate for arts practice and in effect cast them in unreasonable doubt. Themes in current discourse on “arts” and “health” are broadly sketched to provide a context for discussion of arts practices. Approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 34 publications
1
44
0
1
Order By: Relevance
“…A word used in one field or discipline may have different implications in another. The lack of a clear distinction between -for example -what constitutes 'therapy' or 'activity' in both arts and research practice has been identified as contributing to charged debate in arts and health, even placing an 'unreasonable' burden of expectation on arts practice (Broderick, 2011).…”
Section: The Challenges Of Conducting a Literature Review About Methomentioning
confidence: 99%
“…A word used in one field or discipline may have different implications in another. The lack of a clear distinction between -for example -what constitutes 'therapy' or 'activity' in both arts and research practice has been identified as contributing to charged debate in arts and health, even placing an 'unreasonable' burden of expectation on arts practice (Broderick, 2011).…”
Section: The Challenges Of Conducting a Literature Review About Methomentioning
confidence: 99%
“…But, as with other art forms if it is successful, the effects of the work will continue after the play. Evidence-based medicine is the contemporary dominant form of knowledge validation (Broderick, 2011) and Art-based research is just emerging as a counter movement to this approach. At the end of each performance, David Diamond addressed the audience and described the work as a circle that startsin the reality of workshops participants and the casts' lives .…”
Section: Discussionmentioning
confidence: 99%
“…The third seminar, in particular, sought to directly address the need for more theoretical nuance and sophistication in arts and health research to address not only causal relationships, but a deeper understanding of how arts practices function to promote wellbeing (Broderick, 2011). In order to carve out a distinctive intellectual place in an interdisciplinary academy, this seminar challenged researchers to engage further with philosophical reflection on purposes and process, as well as a concern with the quantification of outcomes.…”
Section: Developing Appropriate Theoretical Frameworkmentioning
confidence: 99%